Students' Attitudes toward Communicative Language Teaching (CLT) in English Speaking Intensive Program - Rizky Vita Losi; Muhammad Muslim Nasution (ITScience (Information Technology and Science), 2022)
University students had difficulty with communicative skills, and they must engage in discussion situations in EFL class without adequate skills to speak or write in English. Communicative Language Teaching (CLT) can play an essential role in EFL classes. This study surveyed the students’ attitudes toward Communicative Language Teaching (CLT) in an English-speaking intensive program. Fifteen university students responded to a 20-statement questionnaire as the data. The data was analyzed by using SPSS 20.0 program. The research findings revealed that the students showed positive attitudes toward Communicative Language Teaching (CLT). The students’ felt excited about learning through communicative activities, such as pair and group work, role play, games, etc. This learning satisfaction impacted their willingness to communicate in English. They were also motivated to communicate in English in their class even though they found it was not easy to use CLT, but they kept practising independently. Furthermore, it can be concluded that learning through CLT enabled students to communicate meaningfully, and their attitudes about these communication activities were positively impacted